2005
DOI: 10.4314/tjpr.v2i2.14606
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Studies of antimicrobial activity and chemical constituents of <i>Ximenia americana</i>

Abstract: Purpose: This study was designed to evaluate the relative efficacy of various brands Ximenia americana is a plant that is used in traditional medicine for the treatment of malaria, leproutic ulcers and skin infections of mixed origin in Northern parts of Nigeria. To evaluate the scientific basis for the use of the plant, the antimicrobial activities of extract of the leaves were evaluated against six common bacterial isolates. Chemical constituents of the extract were also determined. The extract of was active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 1 publication
0
49
0
3
Order By: Relevance
“…Salmonella typhi and Escherichia coli were not affected by these extracts. The (James et al, 2007& Ogunleye et al, 2003; few extracts showed also the presence of cyanogenetic glycosides (Ogunleye et al, 2003). Quinones are of the anthraquinone type; terpenes are sesquiterpenes and triterpenes type (Araújo et al, 2008(Araújo et al, , 2009 The methanolic extract was the most active one.…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Salmonella typhi and Escherichia coli were not affected by these extracts. The (James et al, 2007& Ogunleye et al, 2003; few extracts showed also the presence of cyanogenetic glycosides (Ogunleye et al, 2003). Quinones are of the anthraquinone type; terpenes are sesquiterpenes and triterpenes type (Araújo et al, 2008(Araújo et al, , 2009 The methanolic extract was the most active one.…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
“…The results of phytochemical analysis indicated the presence of saponins, flavonoids, tannins and cyanogenetic glycosides. Alkaloids and anthraquinones were not present (Ogunleye et al, 2003). The root, stem bark and leaves aqueous and methanolic extracts of X. americana were tested against five bacteria and they inhibited the growth of Staphylococus aureus and Klebsiella pneumoniae while Shigella flexineri was inhibited by only methanolic leaves, aqueous bark and aqueous leaves extracts.…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Hopea ponga is an endemic tree belonging to Dipterocapaceae family found in tropical ever green forest of western India and it is widely distributed along the Western Ghat of Karnataka. cies under the International Union for Conversation of Nature Red List of threatened species.…”
Section: Introductionmentioning
confidence: 99%